Guinness world records : Amazing animals. - Guinness World Records Limited ([United States] : Guinness World Records Limited, 2017)
Text and photographs present a number of world's records held by animals.
Animal wonders -- Wild things -- On the move -- Celebrity animals -- Animal rescues -- Trick & stunts -- Best in show -- At the zoo -- Peculiar pets -- Animals at work.
School Library Journal, November 2017
5.5
3-6
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Animals -- Miscellanea -- Juvenile literature; World records -- Juvenile literature; Animals -- Miscellanea; World records